A COMPARATIVE STUDY OF DIRECT AND INDIRECT ADDRESS FORMS IN ENGLISH AND UZBEK (Western European Journal of Modern Experiments and Scientific Methods, 2025)
This article is dedicated to the comparative analysis of direct and indirect address forms in English and Uzbek. The study explores the linguistic, pragmatic, and cultural aspects of address forms, analyzing their usage in different speech contexts. In English, formal address forms such as Mr., Ms., and Sir, along with polite expressions, are examined, while in Uzbek, address forms like aka (elder brother), opa (elder sister), and ustoz (teacher), which depend on social status, as well as indirect expressions, are analyzed. The research applies Brown and Levinson’s politeness theory and Leech’s politeness principles to assess the functional characteristics of address forms. The findings contribute to understanding the role of direct and indirect address forms in translation, international communication, and linguistic studies.